A Person‐Centered Approach to Poststroke Care: The COMprehensive Post‐Acute Stroke Services Model. Issue 5 (23rd March 2018) - Bushnell, Cheryl D.; Duncan, Pamela W.; Lycan, Sarah L.; Condon, Christina N.; Pastva, Amy M.; Lutz, Barbara J.; Halladay, Jacqueline R.; Cummings, Doyle M.; Arnan, Martinson K.; Jones, Sara B.; Sissine, Mysha E.; Coleman, Sylvia W.; et al.
Abstract : Many individuals who have had a stroke leave the hospital without postacute care services in place. Despite high risks of complications and readmission, there is no standard in the United States for postacute stroke care after discharge home. We describe the rationale and methods for the development of the COMprehensive Post‐Acute Stroke Services (COMPASS) care model and the structure and quality metrics used for implementation. COMPASS, an innovative, comprehensive extension of the TRAnsition Coaching for Stroke (TRACS) program, is a clinician‐led quality improvement model providing early supported discharge and transitional care for individuals who have had a stroke and have been discharged home. The effectiveness of the COMPASS model is being assessed in a cluster‐randomized pragmatic trial in 41 sites across North Carolina, with a recruitment goal of 6, 000 participants. The COMPASS model is evidence based, person centered, and stakeholder driven. It involves identification and education of eligible individuals in the hospital; telephone follow‐up 2, 30, and 60 days after discharge; and a clinic visit within 14 days conducted by a nurse and advanced practice provider. Patient and caregiver self‐reported assessments of functional and social determinants of health are captured during the clinic visit using a web‐based application. Embedded algorithms immediately construct an individualized care plan. The COMPASS model's pragmatic design and quality metrics may support measurable best practices for postacute stroke care.